Design estratégico e a baixa renda: projetar para habilitar e melhorar as condições de um grupo da zona sul de Porto Alegre - Graúdo, Margarida Maria de Jesus Cardoso (Universidade do Vale do Rio dos Sinos, 2012)
This research sought to contribute in the process of building knowledge of the design and the expansion of it's role as an agent of social change. Understood as a vision of Strategic Design could collaborate as the development of a low-income community in Brazil and studied a group, a community with a low Human development index of South zone of Porto Alegre, composed of women who produce crafts and crafts as a source of income and who were putting together a joint venture of solidarity economy. Through a qualitative approach with ethnographic observations and inspired participation in meetings of the group, were understood its context, its composition and dynamics, identified its characteristics and relationships, its constitution and its potential for social innovation. The goal of this research was to raise elements that collaborate to design a system that enabled the group to improve their craft and development conditions in a sustainable way and creative. Having as leitmotiv Ezio Manzini’s theory of creative communities and enabling systems, it was noted that the Group would have the potential to turn into a creative community. Despite having no party of the Group intend to its formation, the Group presented a participatory approach and mobilized in the search for solutions to their problems. Especially when stimulated by tools used by design and facilitated by the construction of a possible scenario in which raised the necessary elements to build a solution that liaise in their training, with its development and its sustainability. However, the Group would still need to evolve their influence in the design process, being possible through participation in processes of co-creation and after deployment of enabling systems. Because it is a one-off action, despite the craft group raise the necessary elements for your training, was in charge of the construction of bases for researcher a proposal enabling system that considered as premises sharing, empowerment, networking, involve less cost and redemption of common goods. This proposal would still need to be validated or serve as a stimulus for solutions that fully satisfy the needs of the group. Based on this study, the design can strengthen its role as an agent of social transformation, but given the complexity and dimensions of the problems involved in the low-income segment, it is necessary that the design is present continuously, systemic and can develop new collaborative studies and projects to add knowledge on the topic and to the area.
Keywords: Design Estratégico; Inovação Social; Comunidades Criativas; Sistemas Habilitantes; Baixa Renda; Strategic Design; Social Innovation; Creative Communities; Enabling Systems; Low Income; ACCNPQ::Ciências Sociais Aplicadas::Desenho Industrial